A PRE-HOSPITAL ANALYSIS OF PAEDIATRIC MAJOR TRAUMA IN THE GREATER DUBLIN AREA. Issue 12 (18th November 2016) - Kelly, O; O'Reilly, M; Collins, NC
Abstract : Objectives & Background: The provision of both Paediatric and Trauma care in Ireland is undergoing reconfiguration with the formation of a National Children's Hospital (NCH) and Major Trauma Centres and Networks. This will result in the amalgamation of three paediatric emergency departments (EDs) in Dublin into one centralised ED and two satellite centres. Ambulance care in the Greater Dublin Area is provided by Dublin Fire Brigade (DFB) and the National Ambulance Service (NAS). Central to service design and provision is an understanding of demand and patient centred factors. This study aims to study the burden of major paediatric trauma in the Greater Dublin Area as served by DFB in order to inform policy and strategic healthcare planning. Methods: Data from DFB was analysed to determine the incidence of major paediatric trauma in the Dublin area in 2014. 'Major Trauma' was defined as a trauma where the attending paramedics placed the receiving ED on 'standby'. The incident locations were mapped using Central Statistics Office small areas. Data was analysed to determine the median travel time and range to the receiving ED and the proposed NCH, diurnal variation, and the mechanism of injury. Results: DFB responded to 58 paediatric Major Traumas in 2014. Paediatric trauma was focused in suburban areas (Image 1). The median (range) travel time to the current 3 hospitals was 10 mins 15 secs (2'38"–32'12"), this was estimated to change to 18 mins (6'–35') with the opening of a single NCH. 12% of cases occurred between the night time hours of 22:00–07:30. Burns equated for the majority (34.5%) of the incidents, with traffic accidents and falls both accounting for 20.7% (Image 2). Conclusion: The low incidence of paediatric Major Trauma documented in the Greater Dublin Area may reflect the lack of both NAS data and predetermined hospital pre-alert criteria for Major Trauma. Information pertaining to location and timing is vital to hospital staffing procedures and specialty service provision, allowing strategic planning according to likely demand. An awareness of the mechanism of injury of paediatric patients can guide the need for specialist services. The change from the current paediatric service to that of one centralised ED would result in an estimated median increase of 7.75 mins in transit time. It is envisaged that this data can in strategic planning of healthcare provision, particularly at this pivotal moment of reconfiguration in Ireland.Figure 1 Figure 2